Exchange Rate Flexibility, Volatility and the Patterns of Domestic and Foreign Direct Investment - Aizenman, Joshua (IMF Working Papers; Working Paper ;, 1992)
This paper investigates the factors determining the impact of exchange rate regimes on the behavior of domestic investment and foreign direct investment (FDI). Producers may diversify internationally in order to increase the flexibility of production. We characterize the possible equilibria in a macro model that allows for the presence of a short-run Phillips curve. It is shown that a fixed exchange rate regime is more conducive to FDI relative to a flexible exchange rate, and this conclusion applies for both real and nominal shocks. If the dominant shocks are nominal (real) we will observe a negative (a positive) correlation between exchange rate volatility and the level of investment.